Marketing viral, brand awareness e intenção de compra: uma análise das relações existentes a partir de vídeos viralizados - Taino, Rafael (2021)
Viral Marketing is a subject with a high interest from academic and managerial professionals given the reach that a message might conquer and the low cost involved. Studies have investigated the reasons why people share viral content and the type of content with a high likelihood of becoming viral. Regarding the type of content, studies have shown that the ones with an emotional approach, characterized by having the purpose of creating a feeling of emotion in the customer, are more likely to be shared than the ones with an informative approach, defined as the ones with a purpose of sharing any type of instruction to the audience. However, little is known whether virilization has been able to generate brand awareness and influence purchase decision, given that the main purpose of any marketing initiative is to make sure people recognize a specific brand and increase purchase intention. In order to fulfill this knowledge gap, this study investigated whether viral videos were able to generate brand awareness and the correlation between viral marketing, brand awareness and purchase intention in the target customers. Through the application of a survey in a sample of graduation students from PUC/SP that assessed the impact of viral videos, this research has identified that viral videos were able to generate brand awareness and that there is a moderate correlation between brand awareness and purchase intention